Syekh H. Mukhtar Abdul Karim Ambai Dan Pembaharuan Dakwah Di Kerinci - Ahmad Zuhdi (Jurnal Dakwah dan Komunikasi, 2021)
This article aims to review and describe the da'wah figure of Sheikh H. Mukhtar Abdul Karim Ambai as a charismatic cleric in the renewal of Islamic da'wah in Kerinci. This article wants to see what methods are packaged and implemented in their da'wah activities. This title is deliberately presented to remember the services and struggles that have been carried out throughout his life. He preached and educated people to return to practice the teachings of Islam as stated in the Qur'an and the hadith of the Prophet Muhammad. Although there were not a few obstacles and challenges of da'wah that were felt at that time, Sheikh Mukhtar never felt tired. Even in the atmosphere, the Dutch colonial and colonial times were still engulfed. His da'wah strategy is quite easy to accept and practice by the people of Kerinci and its surroundings.